Assessing the Readiness for Building Information Modelling (BIM) Implementation Using the Technology Readiness Index: A Case Study of the Patimban Port Project in West Java, Indonesia - Novi Sudiansyah; Donny Mugia Prayoga (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This research examines the digital transformation challenges in Indonesia’s infrastructure development through a case study of BIM implementation at Patimban Port, West Java. Employing the Technology Readiness Index (TRI) framework, the study measures stakeholder preparedness across four psychological dimensions: (1) optimism toward benefits, (2) willingness to innovate, (3) technical discomfort, and (4) data security concerns. Primary data were gathered through two approaches: (1) a TRI-based questionnaire administered to 47 professionals, and (2) semi-structured interviews with key stakeholders to explore underlying challenges, revealing a paradoxical pattern: while 68% of respondents acknowledged BIM’s strategic value (mean optimism score=2.75), 72% reported implementation hesitancy due to technical skill deficiencies (discomfort score=2.40). The findings offer practical insights for overcoming technology adoption barriers in large-scale infrastructure projects within developing country contexts, particularly addressing the competency gap through targeted training programs.